Approach To The Question Of Truth In The History Of Philosophy - Suhrob Panjiyev (Global Scientific Publishing, 2024)
The article compares comparatively the views of philosophers of modern Western philosophers F. Bacon, R. Descartes, G.V. Leibniz, J. Locke, I. Kant and Hegel on the criterion of truth.
Keywords: Truth; problem; criterion of truth; methodology